Biodiversity conservation on private and communal lands - Sueltenfuss, Jeremy, speaker; Anderson, David, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
How are we doing in conserving Colorado's Biodiversity? How much of it is left? Are there landscapes in Colorado where we still have the basic fabric intact to conserve entire systems? Are there hotspots where actions are more urgent than others? Are there species and places that we've successfully conserved through our actions? What role might private lands play in the big picture for conserving Colorado's biodiversity, now and in the future? What strategies are most likely to be effective given what remains? These are some of the many big questions that The Nature Conservancy (TNC) and the Colorado Natural Heritage Program (CNHP) have worked to answer collaboratively. Our efforts, which culminated in the publication of the State of Colorado's Biodiversity, began as a way to support TNC's Measures of Success Program, but we soon realized that answering these questions would benefit leaders, managers, decision makers, as well as the general public and the private landowners in whose hands so much of our sustainable future rests. With an emphasis on private lands, we will share the results of this work, examine how it is being implemented broadly to support conservation statewide, and how it is serving as a model for other such efforts.
State of Colorado's biodiversity
Moderator: David Anderson.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses